Pseudohallucinations versus hallucinations: wherein lies the difference?. (June 2015) - Wearne, Deborah; Genetti, Amanda
Objective: This paper firstly explores the historical concept of pseudohallucinations and their phenomenology. It then examines the experience of hallucinosis in two subject groups, one with post-traumatic stress disorder with dissociative symptoms and the second with schizophrenia. Method: The two groups were assessed using the Psychotic Symptoms Rating Scale with a view to identifying differences in the hallucinatory and delusional experience. Results: There was no significant difference between the groups in loudness, control, position, duration, or frequency of the voices. Delusions and negative content differed significantly, however. Conclusions: Researchers have started to describe pseudohallucinations along a continuum. We build on this dimensional approach and suggest a collaborative nomenclature for subtyping.